Smart productivity application - Abdul Hakim Abdul Ranie (Nanyang Technological University, 2020)
This report accounts the author’s experience in completing his Final Year Project (FYP) titled ‘Smart Productivity Application’. This report encapsulates the introduction to the project, basic explanations of the methods and ideas being implemented in this project, the overall methodology in developing this mobile application and process of completing this project. This report will go into the detail the development of the entire mobile application from front-end, middleware and back-end and the various programs and programming languages used to complete this project. Lastly this report will encompass the author’s learning journey, achievements and conclusion to his FYP. The purpose of this project is to serve as educational purposes for the author as the author is taking this project as an avenue to broaden and improve on his programming skills. The codes in this project were all written by the author himself through the one-year process of the FYP. The project is purely for educational purposes, but it can prove to be a guide for anyone interested to learn more about the development of Mobile Applications. The name of the application is ‘Productivita’ and this will be crucial as the names of the author’s database and project structure will be following the name of the application.